Analisis Yuridis Restorative Justice Dalam Perkara Tawuran Antar Pelajar di Kota Medan - R. Rizki; Kevin Christian Simanjuntak; Ridho Perdana Sembiring (Jurnal Interpretasi Hukum, 2024)
Student brawls are a social phenomenon that continues to occur in various regions, including Medan City. This phenomenon is not merely a conflict between individuals or groups but also reflects various social, economic, and cultural factors that contribute to the formation of aggressive behavior among teenagers. Student brawls often lead to violence, destruction of public facilities, and even casualties. Therefore, a legal approach is needed that not only emphasizes a repressive aspect through criminal prosecution but also an alternative approach that focuses more on recovery and prevention, one of which is Restorative Justice.The Restorative Justice approach in Indonesia’s juvenile criminal justice system is regulated under Law Number 11 of 2012 on the Juvenile Criminal Justice System (UU SPPA). This concept prioritizes case resolution through mediation and dialogue between offenders, victims, and the affected community. Restorative Justice aims to restore disrupted social relationships due to criminal acts, provide offenders with the opportunity to take responsibility for their actions, and minimize the negative impact of the conventional criminal justice system on children in conflict with the law.